Grotesque Representations of Former President Jair Bolsonaro: Semiodiscoursive Issues (Global Journal of Human-Social Science, 2023)
This article investigates the aesthetics of the grotesque used in images of former President Jair Bolsonaro published in Facebook groups from the semiodiscursive tensive approach demonstrating the pertinence of these points of view for the expansion of comprehension of this aesthetic as a semi-social and semi-discursive practice From the generative course of meaning and the tensive mode style of the text we demonstrate that the grotesque can be considered a genre style modalized and stylized in narrative structures and a tensive rhetoric The texts analyzed are generated by phoric thymic thematic and figurative paths typical of the genre mythologically related to the fundamental semantic values life death and nature culture being articulated in tensive syntactic modes and styles and used not only as social criticism but the establishment of a semantic program which attempts to disrupt the current one
Keywords: rhetoric of the event grotesque discourse semiotics former president bolsonaro